Expression of toll-like receptors (tlrs) in the equine peripheral blood mononuclear cells (pbmcs) during the early pregnancy and estrous cycle - Ercan Kurar; Mehmet Osman Atli; Aydin Guzeloglu; Seyit Ali Kayis; Ahmet Semacan (Eurasian Journal of Veterinary Sciences)
Aim: Practical, reliable and economical pregnancy diagnosis method for as early as possible time of pregnancy in mares is still requirement. Immune tolerance against allogenic fetus is critically important during the early pregnancy. Tolllike Receptors (TLRs) are known to be an important part of innate immune system. Aim was to evaluate expression of TLRs in peripheral blood mononuclear cells (PBMCs) during the early pregnancy in mare. Material and Methods: Blood samples were collected on days of ovulation (d0) and 8 during estrous and pregnancy from three same mares. Total RNA samples were isolated from PBMCs and cDNA synthesis was performed. Expressions of TLRs at mRNA levels were quantified by using realtime RT-PCR in duplicates. Relative Expression Software Tool (REST2009) was used for statistical analysis. Results: TLRs (1 to 10) were found to be expressed in PMBCs by RT-PCR. However, real-time PCR measurements failed to show effects of pregnant or cyclic status on expression of TLRs. Conclusion: According to these results, it may suggest that determination of TLRs gene expression in equine PBMCs during early pregnancy is not a good marker in understanding early equine pregnancy.